Reconstruction of the Authority of the Administrative Court (Ptun) To Ad-judicate Positive Fictitious Decisions - Laksono, Nowo; Nasution, Krisnadi; Budiarsih (Law and Economics, 2025)
This research discusses the lack of effectiveness in the authority of the State Administrative Tribunal (PTUN) in handling disputes arising from positive fictitious decisions, as regulated in Law Number 30 of 2014 on Government Administration. This law emphasizes PTUN's role in providing legal certainty for decisions that are deemed legally granted despite the absence of a response from the relevant authorities. Although PTUN has jurisdiction over such disputes, the overly formalistic procedural approach often leads to lawsuits being dismissed or deemed inadmissible, contradicting the principles of modern administrative justice.This study aims to reconstruct PTUN's authority to enhance its effectiveness in adjudicating cases involving positive fictitious decisions. A normative juridical approach is applied by examining applicable legal provisions, analyzing court rulings, and referring to relevant legal literature. The findings indicate that procedural rigidity and normative ambiguity remain significant obstacles, particularly in determining the object of the dispute and proving the silence of government officials or agencies. This research offers a conceptual reconstruction of PTUN's authority, advocating for a more progressive judicial interpretation and the enforcement of the due process of law principle. Strengthening PTUN’s role is expected to improve administrative accountability, expand public access to justice, and provide better legal certainty in addressing uncertainties arising from government inaction